Evaluation of E-Commerce Website Functionality Using a Mamdani Fuzzy System - Al-Qaisi, L.; Mesleh, A.; Al-Qaisi, A.; Sharadqh, A.; Zahran, B.; Alkasassbeh, J.; Olaimat, M. (Engineering, Technology & Applied Science Research, 2015)
The majority of leader companies are running their businesses using online E-commerce websites. These E-commerce websites are becoming significant revenue drivers and major retailers. Hence, it is critical to evaluate the functionality of these websites which are expected to support growing business needs. The evaluation of the functionality of E-commerce websites is not a straightforward process due to the many constraints and standards that should be considered. Fuzzy logic is a powerful technique used in modeling impreciseness and uncertainties. This paper proposes a Mamdani fuzzy system that evaluates the functionality of E-commerce websites over different parameters: accuracy, flexibility, client support, and availability of product information. Experimental results provide positive relations between accuracy and flexibility on the functionality of E-commerce websites.